Royal Miscarriage - Adesanya, Gbenga (Literamed Publications Nigeria Ltd, 2008)
Royal Miscarriage-King Ojuda ascended the throne of his father against the wish of the oracle. His rule was characterized by tyranny and despotism. His involvement with Arewa brought about a dramatic turn in his quest for prolonged rulership.
Keywords: Drama; Nigeria(English)